Kadar Malondialdehyde Induk dan Struktur Morfologis Fetus Mencit (Mus musculus) yang Diperdengarkan Murottal dan Musik Rock pada Periode Gestasi - Tri Rima Setyawati, Silvie Kurniasari, Ari Hepi Yanti, (Jurnal Protobiont, 2017)
Gestation is a stressful state that involved physiological change. Environmental stressor could alter the adaptive mechanism during gestation, thus bring bad impact to the developing fetus. Music is commonly used as a therapy media to minimize stress during gestation. This research aims to examine the effect of listening murottal and rock music during gestation towards levels of oxidative stress in mouse dams (Mus musculus) and the morphological structure of the fetuses. The levels of oxidative stress were analyzed by measuring malondialdehyde (MDA) level as the biomarker. This research was conducted from July to November 2016 in Zoology Laboratory and Chemical Laboratory of Faculty of Mathematics and Natural Sciences Tanjungpura University Pontianak. Fifteen mice were divided into 2 experimental groups (murottal/M and rock/R) and 1 control group (K). During day 0 to day 15 of gestation, the pregnant mouse dams in group M and R were exposed to murottal and rock music, respectively. Laparatomy was conducted on the 16th day of gestation, followed by serum MDA measurements and observing the fetuses. According to the result, MDA level in group M was significantly lower (0.42±0.21 nmol/mL; p<0.05) than two other groups. This result accompanied by the normal fetuses with highest mean of weight (0.74±0.05 g) and length (18.72±0.90 mm) compared to fetuses from group R and K. Fetus with hemorrhage and intrauterine growth restriction (IUGR) were found in group R, while intrauterine mortality was found in group R and K.